2015
DOI: 10.5772/61147
|View full text |Cite
|
Sign up to set email alerts
|

Efficient, Green Non-Aqueous Microwave-Assisted Synthesis of Anatase TiO2 and Pt Loaded TiO2 Nanorods with High Photocatalytic Performance

Abstract: A high-yield synthesis of pure anatase titania nanorods has been achieved through a nonaqueous microwave-based approach. The residual organics on nanoparticles surfaces were completely removed under ozone flow at room temperature in air. The TiO2 nanorods, with average lengths of 27.6 ± 5.8 nm and average diameters of 3.2 ± 0.4 nm, were characterized by powder X-Ray diffraction, transmission electron microscopy, selected area diffraction, BET surface area analysis and FT-IR spectroscopy. The photocatalytic per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…S5) belonged to the type IV (IUPAC classification) with a distinct type H3 hysteresis loop at a relative pressure range of (0.7-1.0) for HNT and H95T5 and of (0.4-0.9) for TiO2. This indicated that their mesoporous and microporous structures were preserved [74][75][76][77][78][79][80] .…”
Section: 1morphological and Structural Characterizationmentioning
confidence: 92%
“…S5) belonged to the type IV (IUPAC classification) with a distinct type H3 hysteresis loop at a relative pressure range of (0.7-1.0) for HNT and H95T5 and of (0.4-0.9) for TiO2. This indicated that their mesoporous and microporous structures were preserved [74][75][76][77][78][79][80] .…”
Section: 1morphological and Structural Characterizationmentioning
confidence: 92%
“…34,36,[40][41][42][43][44][45] Current study proposed the use of Cymbopogon citratus (commonly known as lemongrass) leaf extract as reducing of metal precursors and capping agent, due to the high content of phytochemicals such as neral, citral, geranial, pinito, allantoin flavonoids, hydrocarbons, waxy esters, sterol esters, ketones, aldehydes, terpenoids, phenols, fatty alcohols, fatty acids, among others. [46][47][48][49][50][51][52] This plant is widely available in tropical and semitropical environment zones throughout Asia, Africa, and South America. 53,54 Therefore, lemongrass leaves were proposed to be part of the raw material in the synthesis of TiO 2 and ZnO nanoparticles since they are easily found in the Department of Bolivar (Cartagena, Colombia) and are no part of the food chain.…”
Section: Introductionmentioning
confidence: 99%